Footstep analysis at different slopes and speeds in elite race walking - Padulo, J.; Annino, G.; D'Ottavio, S.; Vernillo, G.; Smith, L.; Migliaccio, G. M.; Tihanyi, J. (The Journal of Strength and Conditioning Research, 2013)
In order to investigate the effects of speed and slope on kinematic parameters, we studied the step parameters of 12 elite race walkers on a treadmill at different speeds (3.61, 3.89, and 4.17 m/s) and slopes (0, 2, and 7%). A high-speed digital camera (210 Hz) was used to record motion, and 2D data were analyzed with Dartfish 5.5Pro. The parameters studied were step length (SL), step frequency (SF), and contact time (CT). The results showed that the increases in SL were linearly related to increases in speed: r = 0.37 with p < 0.01, whereas decreases in SL were elicited with an increase in slope r = -0.56, p < 0.0001 ([0-2% = -3.5%, p < 0.02], [0-7% = -7.5%, p < 0.01]). The SF was positively correlated with increases in speed, r = 0.56, p = 0.0001, and slopes, r = 0.50, p < 0.0001 (0-2% = 3.6% n.s.; 0-7% = 8.5%, p < 0.01). Conversely, CT was negatively correlated with increases of both speed; r = -0.57, p < 0.0001 and slope r = -0.50, p < 0.0001 (0-2% = -3.4%, n.s.; 0-7% = -7.7%, p < 0.01). These results suggest that using slopes <7% could considerably alter the neuromechanical behavior of athletes, whereas slopes around 2% could positively influence the performance of the elite race walkers without altering the race-walking technique.